The legal framework for the process of monitoring the electoral register a In the comparative countries and Iraq : A Comparative Study - Abd Alrazaq, Mahmood; Younes, Maha (Journal of Legal Sciences, 2023)
This study entitled (The legal framework for the process of monitoring the electoral register (a comparative study between Egypt and Iraq)) shows the importance of monitoring the right to participate in political life and public affairs، as all electoral legislation in democratic countries is keen on the integrity، integrity and legitimacy of elections، and one of the most important guarantees of this  Existence of effective oversight at every stage of the electoral process، including the preliminary stage. Oversight is the process of collecting and inventorying information about the electoral processes in all its stages، by following an organized mechanism in collecting information on each stage، which is then used to issue objective and impartial assessments on the extent of safety، integrity، and fairness.  The electoral process and the integrity and validity of the registration process in the electoral register. We have tried to answer the questions and problems that we raised in the introduction to the research by identifying how to monitor the register، who are the competent authorities for oversight، what is meant by electoral crimes، especially electoral register crimes، grievance procedures and appeals against records، and we havedealt with all of the foregoing in a comparative study between Egypt and Iraq.